Benzothiadiazole copolymer as well as preparation method and application thereof
By using benzothiadiazole copolymer to prepare perovskite solar cells, the problems of poor stability and low conversion efficiency of perovskite solar cells in harsh environments are solved, and high-efficiency energy conversion and long-term stability are achieved.
Patent Information
- Application Number
- CN202510001142.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
AI Technical Summary
Perovskite solar cells have poor stability in environments such as excessive humidity and overheating of temperature, and their battery conversion efficiency is difficult to improve, which limits their development.
The perovskite solar cells are prepared by using benzothiadiazole copolymer as a material, which improves the output voltage, filling factor and short-circuit current density of the battery, thereby improving the energy conversion efficiency of the battery and maintaining long-term stability in the atmospheric environment.
It realizes the efficient energy conversion and long-term stability of perovskite solar cells, and improves the overall performance of the battery.
Smart Images

Figure CN119708443A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic polymer copolymers, and in particular relates to a benzothiadiazole copolymer and a preparation method and application thereof. Background Art
[0002] As the demand for renewable energy increases, solar energy, as a stable and infinitely distributed natural resource, has become particularly important in the field of new energy. Among them, perovskite solar cells are devices that directly convert light energy into electrical energy through the photoelectric effect or photochemical reaction, and have become a very promising new photovoltaic device in the field of new energy.
[0003] In recent years, perovskite solar cells have developed rapidly due to their significant advantages such as environmental protection and low production cost. However, under the influence of excessive humidity, overheating and other environmental factors, perovskite solar cells are easy to decompose, have poor stability, and generally have problems such as difficulty in improving battery conversion efficiency. The development of perovskite solar cells has been subject to certain restrictions.
[0004] Poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) is a common hole transport material and is widely used in the preparation of perovskite solar cells. However, due to the strong hydrophobicity of PTAA as a hole transport material, it does not ensure uniform nucleation of perovskite grown on its surface to achieve high open circuit voltage and fill factor of perovskite solar cells, and its long-term stability is poor. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a benzothiadiazole copolymer and a preparation method and application thereof. The present invention uses the benzothiadiazole copolymer to prepare a perovskite solar cell, and the prepared perovskite solar cell has a higher output voltage, fill factor, and short-circuit current density, thereby having a higher battery energy conversion efficiency; in addition, the perovskite solar cell prepared by the benzothiadiazole copolymer of the present invention can be used for a long time in an atmospheric environment and can maintain a high stability.
[0006] The object of the present invention is to provide a benzothiadiazole copolymer, the structural formula of the benzothiadiazole copolymer is shown in formula (I):
[0007]
[0008] Formula (I);
[0009] Among them, x:y is 5~50:1.
[0010] In some embodiments of the present invention, the x:y is 20-45:1.
[0011] In some embodiments of the present invention, the x:y is 25-35:1.
[0012] In some embodiments of the present invention, the number average molecular weight of the benzothiadiazole copolymer is 12000-20000 g / mol, and the PDI is 1.5-2.5.
[0013] In some embodiments of the present invention, the value range of x is 10-500, and the value range of y is 1-10.
[0014] Another object of the present invention is to provide a method for preparing a benzothiadiazole copolymer, comprising the following steps:
[0015] The dibromo-substituted triphenylamine compound, the benzothiadiazole pinacol borate compound, the triphenylamine pinacol borate compound, the auxiliary agent and the palladium catalyst are mixed and reacted at elevated temperature to obtain the benzothiadiazole copolymer.
[0016] The structural formula of the dibromo-substituted triphenylamine compound is shown in formula (II):
[0017]
[0018] Formula (II);
[0019] The benzothiadiazole boronic acid pinacol ester compound is shown in formula (III):
[0020]
[0021] Formula (III);
[0022] The triphenylamine boric acid pinacol ester compound is shown in formula (IV):
[0023]
[0024] Formula (IV);
[0025] The structural formula of the palladium catalyst is shown in formula (V):
[0026]
[0027] Formula (V).
[0028] In some embodiments of the present invention, the molar ratio of the dibromo-substituted triphenylamine compound, the benzothiadiazole boric acid pinacol ester compound, and the triphenylamine boric acid pinacol ester compound is 1-3:1-3:1-4.
[0029] In some embodiments of the present invention, the total molar ratio of the dibromo-substituted triphenylamine compound, the benzothiadiazole boronic acid pinacol ester compound and the triphenylamine boronic acid pinacol ester compound to the molar ratio of the palladium catalyst is 1:0.001-0.01.
[0030] In some embodiments of the present invention, the reaction temperature is 80-120° C. and the reaction time is 12-32 hours.
[0031] In some embodiments of the present invention, the auxiliary agent includes an inorganic base, an organic phosphine, a quaternary ammonium salt and a solvent.
[0032] In some embodiments of the present invention, the inorganic base is selected from at least one of potassium carbonate and potassium phosphate.
[0033] In some embodiments of the present invention, the organic phosphine is selected from at least one of tri(2-furyl)phosphine and tributylphosphine.
[0034] In some embodiments of the present invention, the quaternary ammonium salt is selected from at least one of tetrabutylammonium bromide and methyltrialkylammonium chloride.
[0035] In some embodiments of the present invention, the solvent is a mixture of toluene and water.
[0036] In some embodiments of the present invention, the volume ratio of the toluene to the water is 2-8:1-2.
[0037] In some embodiments of the present invention, the total mole ratio of the dibromo-substituted triphenylamine compound, the benzothiadiazole pinacol borate compound and the triphenylamine pinacol borate compound to the mole ratio of the inorganic base is 1-1.5:1-1.5.
[0038] In some embodiments of the present invention, the total molar ratio of the dibromo-substituted triphenylamine compound, the benzothiadiazole pinacol borate compound and the triphenylamine pinacol borate compound to the molar ratio of the organic phosphine is 1.5-4.5:1.
[0039] In some embodiments of the present invention, the total molar ratio of the dibromo-substituted triphenylamine compound, the benzothiadiazole pinacol borate compound and the triphenylamine pinacol borate compound to the molar ratio of the quaternary ammonium salt is 1:0.01-0.1.
[0040] Another object of the present invention is to provide an application of the benzothiadiazole copolymer or the benzothiadiazole copolymer prepared by the preparation method of the benzothiadiazole copolymer in the preparation of perovskite solar cells.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] (1) The method for preparing the benzothiadiazole copolymer provided by the present invention can obtain a benzothiadiazole copolymer with a high yield.
[0043] (2) The perovskite solar cell prepared by the benzothiadiazole copolymer provided by the present invention has a higher Voc value, Jsc value, and FF value, thereby being able to obtain a high PCE value and having a higher battery energy conversion efficiency.
[0044] (3) The perovskite solar cell prepared by the benzothiadiazole copolymer provided by the present invention can maintain a high battery energy conversion efficiency during long-term use, and can maintain a high stability in the atmospheric environment for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The accompanying drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation of the present application. In the accompanying drawings:
[0046] Figure 1 This is the H NMR spectrum of the benzothiadiazole copolymer prepared in Example 4.
[0047] Figure 2 This is the NMR carbon spectrum of the benzothiadiazole copolymer prepared in Example 4. DETAILED DESCRIPTION
[0048] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0049] All raw materials of the present invention can be obtained through commercial channels.
[0050] The structure of the palladium catalyst used in all embodiments of the present invention for preparing benzothiadiazole copolymers is as follows:
[0051]
[0052] The structure of the dibromo-substituted triphenylamine compound used in all embodiments of the present invention for preparing benzothiadiazole copolymers is as follows:
[0053] ;
[0054] The structure of the benzothiadiazole boric acid pinacol ester compound used in all embodiments of the present invention for preparing benzothiadiazole copolymers is as follows:
[0055] ;
[0056] The structure of the triphenylamine boric acid pinacol ester compound used in all embodiments of the present invention for preparing benzothiadiazole copolymers is as follows:
[0057] .
[0058] Example 1
[0059] This embodiment provides a dibromo-substituted triphenylamine compound, and the preparation method thereof comprises the following steps:
[0060] 2,4,6-aniline (2mmol), 4-bromoiodobenzene (4.4mmol), potassium tert-butoxide (4mmol), and di(tri-tert-butyl)palladium (0.05mmol) were added to a clean 100 mL reaction bottle in sequence, and 40 mL of toluene was added as solvent. The reaction was refluxed at 110°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature, the product was filtered, the filtrate was concentrated, separated by column chromatography, and dried to obtain a dibromo-substituted triphenylamine compound.
[0061] Example 2
[0062] This embodiment provides a triphenylamine boric acid pinacol ester compound, and the preparation method thereof comprises the following steps:
[0063] Dibromo-substituted triphenylamine compound (5 mmol), biboric acid pinacol ester (12 mmol), tri(2-furyl)phosphine (0.5 mmol), Pd(dppf)Cl 2 (0.4mmol), potassium carbonate (10mmol), and 1,4-epoxyhexadecane (40mL) were placed in a clean 100mL reaction bottle, heated to 100°C and refluxed for 12 hours; after the reaction was cooled, the product was filtered, the filtrate was concentrated, separated by column chromatography, and dried to obtain a triphenylamine boric acid pinacol ester compound.
[0064] Example 3
[0065] This embodiment provides a benzothiadiazole boric acid pinacol ester compound, and the preparation method thereof comprises the following steps:
[0066] 4,7-Dibromo-2,1,3-benzothiadiazole (5 mmol), biboric acid pinacol ester (12 mmol), tri(2-furyl)phosphine (0.5 mmol), Pd(dppf)Cl 2(0.4mmol), potassium carbonate (10mmol), and 1,4-epoxyhexadecane (40mL) were placed in a clean 100mL reaction bottle, heated to 100°C and refluxed for 12 hours; after the reaction was cooled, the product was filtered, the filtrate was concentrated, separated by column chromatography, and dried to obtain a benzothiadiazole boronic acid pinacol ester compound.
[0067] Example 4
[0068] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0069] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (4.4 mmol), a benzothiadiazole pinacol boronic acid ester compound (4.4 mmol), a triphenylamine pinacol boronic acid ester compound (4.4 mmol), tributylphosphine (5.3 mmol), potassium carbonate (15.2 mmol) and methyltrialkylammonium chloride (0.13 mmol) in the reaction bottle, add 30 mL of toluene and 20 mL of water, and use nitrogen to deoxygenate for 30 minutes; add a palladium catalyst (0.04 mmol), heat to 100°C and continue the reaction for 24 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 67%; the PDI of the benzothiadiazole copolymer is 2.5, and the number average molecular weight is 18320 g / mol.
[0070] The structure of the benzothiadiazole copolymer is shown below:
[0071]
[0072] Among them, x=95.24mmol%, y=4.76mmol%.
[0073] Example 5
[0074] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0075] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (3.8 mmol), a benzothiadiazole pinacol boronic acid ester compound (3.8 mmol), a triphenylamine pinacol boronic acid ester compound (3.8 mmol), tributylphosphine (7.6 mmol), potassium carbonate (14 mmol) and methyltrialkylammonium chloride (0.34 mmol) in the reaction bottle, add 45 mL of toluene and 10 mL of water, and deoxygenate with nitrogen for 30 minutes; add a palladium catalyst (0.57 mmol), heat to 110°C and continue the reaction for 18 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 59%; the PDI of the benzothiadiazole copolymer is 1.8, and the number average molecular weight is 18216 g / mol.
[0076] The structure of the benzothiadiazole copolymer is shown below:
[0077]
[0078] Among them, x=93.75mmol%, y=6.25mmol%.
[0079] Example 6
[0080] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0081] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (4.2 mmol), a benzothiadiazole pinacol boronic acid ester compound (4.2 mmol), a triphenylamine pinacol boronic acid ester compound (4.2 mmol), tributylphosphine (7.8 mmol), potassium carbonate (18 mmol) and methyltrialkylammonium chloride (0.15 mmol) in the reaction bottle, add 40 mL of toluene and 20 mL of water, and use nitrogen to deoxygenate for 30 minutes; add a palladium catalyst (0.1 mmol), heat to 120°C and continue the reaction for 16 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 58%; the PDI of the benzothiadiazole copolymer is 2.0, and the number average molecular weight is 13260 g / mol.
[0082] The structure of the benzothiadiazole copolymer is shown below:
[0083]
[0084] Among them, x=96.77mmol%, y=3.23mmol%.
[0085] Example 7
[0086] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0087] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (5 mmol), a benzothiadiazole pinacol boronic acid ester compound (5 mmol), a triphenylamine pinacol boronic acid ester compound (5 mmol), tributylphosphine (6 mmol), potassium carbonate (18 mmol) and methyltrialkylammonium chloride (0.15 mmol) in the reaction bottle, add 40 mL of toluene and 20 mL of water, and deoxygenate with nitrogen for 30 minutes; add a palladium catalyst (0.1 mmol), heat to 120°C and continue the reaction for 16 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 58%; the PDI of the benzothiadiazole copolymer is 2.0, and the number average molecular weight is 15827 g / mol.
[0088] The structure of the benzothiadiazole copolymer is shown below:
[0089]
[0090] Among them, x=98.04mmol%, y=1.96mmol%.
[0091] Example 8
[0092] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0093] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (3.2 mmol), a benzothiadiazole pinacol boronic acid ester compound (3.2 mmol), a triphenylamine pinacol boronic acid ester compound (3.2 mmol), tributylphosphine (6.5 mmol), potassium carbonate (12 mmol) and methyltrialkylammonium chloride (0.98 mmol) in the reaction bottle, add 50 mL of toluene and 10 mL of water, and use nitrogen to deoxygenate for 30 minutes; add a palladium catalyst (0.08 mmol), heat to 100°C and continue the reaction for 20 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 61%; the PDI of the benzothiadiazole copolymer is 2.2, and the number average molecular weight is 15827 g / mol.
[0094] The structure of the benzothiadiazole copolymer is shown below:
[0095]
[0096] Among them, x=96.15mmol%, y=3.85mmol%.
[0097] Example 9
[0098] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0099] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (4.5 mmol), a benzothiadiazole pinacol boronic acid ester compound (4.5 mmol), a triphenylamine pinacol boronic acid ester compound (4.5 mmol), tributylphosphine (6.8 mmol), potassium carbonate (16 mmol) and methyltrialkylammonium chloride (0.68 mmol) in the reaction bottle, add 40 mL of toluene and 10 mL of water, and deoxygenate with nitrogen for 30 minutes; add a palladium catalyst (0.03 mmol), heat to 110°C and continue the reaction for 18 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 60%; the PDI of the benzothiadiazole copolymer is 2.1, and the number average molecular weight is 16385 g / mol.
[0100] The structure of the benzothiadiazole copolymer is shown below:
[0101]
[0102] Among them, x=97.22mmol%, y=2.78mmol%.
[0103] Example 10
[0104] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0105] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (3.6 mmol), a benzothiadiazole pinacol boronic acid ester compound (3.6 mmol), a triphenylamine pinacol boronic acid ester compound (3.6 mmol), tributylphosphine (7.2 mmol), potassium carbonate (14 mmol) and methyltrialkylammonium chloride (0.75 mmol) in the reaction bottle, add 60 mL of toluene and 10 mL of water, and use nitrogen to deoxygenate for 30 minutes; add a palladium catalyst (0.03 mmol), heat to 90°C and continue the reaction for 22 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 54%; the PDI of the benzothiadiazole copolymer is 2.4, and the number average molecular weight is 14759 g / mol.
[0106] The structure of the benzothiadiazole copolymer is shown below:
[0107]
[0108] Among them, x=92.24mmol%, y=7.76mmol%.
[0109] Embodiment 11
[0110] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0111] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (4.8 mmol), a benzothiadiazole pinacol boronic acid ester compound (4.8 mmol), a triphenylamine pinacol boronic acid ester compound (4.8 mmol), tributylphosphine (5.2 mmol), potassium carbonate (16 mmol) and methyltrialkylammonium chloride (0.43 mmol) in the reaction bottle, add 50 mL of toluene and 10 mL of water, and use nitrogen to deoxygenate for 30 minutes; add a palladium catalyst (0.02 mmol), heat to 80°C and continue the reaction for 30 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 55%; the PDI of the benzothiadiazole copolymer is 2.5, and the number average molecular weight is 15521 g / mol.
[0112] The structure of the benzothiadiazole copolymer is shown below:
[0113]
[0114] Among them, x=83.33mmol%, y=16.67mmol%.
[0115] Example 12
[0116] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0117] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (5.4 mmol), a benzothiadiazole pinacol boronic acid ester compound (5.4 mmol), a triphenylamine pinacol boronic acid ester compound (5.4 mmol), tributylphosphine (3.6 mmol), potassium carbonate (18 mmol) and methyltrialkylammonium chloride (0.16 mmol) in the reaction bottle, add 40 mL of toluene and 5 mL of water, and use nitrogen to deoxygenate for 30 minutes; add a palladium catalyst (0.02 mmol), heat to 100°C and continue the reaction for 28 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 65%; the PDI of the benzothiadiazole copolymer is 1.9, and the number average molecular weight is 13414 g / mol.
[0118] The structure of the benzothiadiazole copolymer is shown below:
[0119]
[0120] Among them, x=91.15mmol%, y=8.85mmol%.
[0121] Embodiment 13
[0122] This embodiment provides a benzothiadiazole copolymer, and the preparation method thereof comprises the following steps:
[0123] Take a clean 150 mL reaction bottle, place a dibromo-substituted triphenylamine compound (5.2 mmol), a benzothiadiazole pinacol boronic acid ester compound (5.2 mmol), a triphenylamine pinacol boronic acid ester compound (5.2 mmol), tributylphosphine (3.8 mmol), potassium carbonate (16 mmol) and methyltrialkylammonium chloride (0.32 mmol) in the reaction bottle, add 30 mL of toluene and 20 mL of water, and use nitrogen to deoxygenate for 30 minutes; add a palladium catalyst (0.02 mmol), heat to 90°C and continue the reaction for 32 hours; after the reaction is cooled to room temperature, methanol is added to the product for precipitation, washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain a benzothiadiazole copolymer with a yield of 62%; the PDI of the benzothiadiazole copolymer is 2.2, and the number average molecular weight is 15630 g / mol.
[0124] The structure of the benzothiadiazole copolymer is shown below:
[0125]
[0126] Among them, x=90.91mmol%, y=9.09mmol%.
[0127] Comparative Example 1
[0128] This comparative example provides a poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], the preparation method of which comprises the following steps:
[0129] S1. Add 3,4,5-trimethylaniline (2mmol), 4-bromoiodobenzene (4.4mmol), potassium tert-butoxide (4mmol), and di(tri-tert-butyl)palladium (0.05mmol) into a clean 100 mL reaction bottle in sequence, add 40mL of toluene as solvent, reflux at 110°C for 6 h, cool to room temperature after the reaction, filter the product, concentrate the filtrate, separate by column chromatography, and dry to obtain compound A;
[0130] S2. Compound A (5 mmol), bipyraclostrobin (12 mmol), tri(2-furyl)phosphine (0.5 mmol), Pd(dppf)Cl2 (0.4 mmol), potassium carbonate (10 mmol), and 1,4-epoxyhexadecane (40 ml) were placed in a clean 100 mL reaction bottle, heated to 100 °C and refluxed for 12 h; after the reaction was cooled, the product was filtered, the filtrate was concentrated, separated by column chromatography, and dried to obtain compound B;
[0131] S3. Compound A (5 mmol), compound B (5 mmol), tri(2-furyl)phosphine (0.08 mmol), potassium carbonate (15 mmol) and tetrabutylammonium bromide (0.5 mmol) were placed in a clean 150 mL reaction bottle, 30 mL of toluene and 10 mL of water were added, and nitrogen was used for deoxygenation for 30 minutes; pyridine carboxaldehyde palladium catalyst (0.05 mmol) was added, and the mixture was heated to 100° C. and the reaction was continued for 12 hours; after the reaction was cooled to room temperature, methanol was added to the product for precipitation, and the product was washed with water, washed with alcohol, extracted with n-hexane, and dried to obtain poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine];
[0132] The structural formula of the pyridine carboxaldehyde palladium catalyst is as follows:
[0133] ;
[0134] The structural formula of the poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is as follows:
[0135]
[0136] The number average molecular weight of the poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is 8345 g / mol, and the PDI is 2.5.
[0137] Embodiment 14
[0138] This embodiment provides a pin-type perovskite solar cell, the specific cell structure is ITO / benzothiadiazole copolymer / perovskite active layer / PCBM / BCP / Ag, and the specific implementation steps are as follows:
[0139] (1) Cleaning of the transparent substrate layer: First, take out the ITO transparent conductive glass, tear off the plastic protective film on the surface, and first use detergent to gently wipe the surface oil and dirt, and then ultrasonically clean it in a 0.2 wt% detergent aqueous solution, deionized water, and isopropanol for 15 min respectively. Finally, use nitrogen to blow dry the isopropanol on the ITO surface and put it in a box for later use.
[0140] (2) Deposition of hole transport layer: The benzothiadiazole copolymer of Example 4 was prepared into a 2.5 mg / mL precursor solution, the solvent was chlorobenzene, the cleaned ITO was first placed in an ultraviolet ozone cleaner for surface hydrophilic treatment, and then the precursor solution was sucked out with a pipette to evenly cover the ITO surface, and then coated on the ITO glass by scraping.
[0141] (3) Preparation of perovskite active layer: FAPbI 3 The system perovskite precursor liquid is sucked out with a pipette and evenly covered on the surface of the wetting layer. The perovskite active layer is formed by a combination of scraping + flash evaporation, and then annealed at 100 °C on a hot stage for 30~60 min.
[0142] (4) Deposition of electron transport layer: Weigh 20 mg of PCBM and add 1 mL of chlorobenzene to prepare the precursor solution of the electron transport layer. The electron transport layer precursor solution is deposited on the surface of the perovskite active layer by scraping.
[0143] (5) Deposition of hole blocking layer: Weigh 8 mg of BCP and add 16 mL of isopropanol to prepare a precursor solution. Then, the prepared precursor solution is aspirated with a pipette and evenly covered on the surface of the hole blocking layer, and then deposited on the surface of the electron transport layer by scraping.
[0144] (6) Deposition of metal electrode layer: A 100 nm thick Ag film was thermally evaporated under high vacuum at an evaporation rate of 0.3 Å / s for 20 nm and then deposited on the surface of the hole blocking layer at 1 Å / s to a thickness of 100 nm.
[0145] Embodiment 15
[0146] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 5" to obtain the pin-type perovskite solar cell of Embodiment 15.
[0147] Example 16
[0148] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 6", thereby obtaining the pin-type perovskite solar cell of Embodiment 16.
[0149] Embodiment 17
[0150] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 7", thereby obtaining the pin-type perovskite solar cell of Embodiment 17.
[0151] Embodiment 18
[0152] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 8" to obtain the pin-type perovskite solar cell of Embodiment 18.
[0153] Embodiment 19
[0154] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 9" to obtain the pin-type perovskite solar cell of Embodiment 19.
[0155] Embodiment 20
[0156] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 10", thereby obtaining the pin-type perovskite solar cell of Embodiment 20.
[0157] Embodiment 21
[0158] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 11", thereby obtaining the pin-type perovskite solar cell of Embodiment 21.
[0159] Embodiment 22
[0160] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 12", thereby obtaining the pin-type perovskite solar cell of Embodiment 22.
[0161] Embodiment 23
[0162] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 14 in that the "benzothiadiazole copolymer of Embodiment 4" in step (2) of Embodiment 14 is replaced with "benzothiadiazole copolymer of Embodiment 13" to obtain the pin-type perovskite solar cell of Embodiment 23.
[0163] Comparative Example 2
[0164] This comparative example provides a pin-type perovskite solar cell, which is different from Example 14 in that the "benzothiadiazole copolymer of Example 4" in step (2) of Example 14 is replaced with "poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] of Comparative Example 1", thereby obtaining the pin-type perovskite solar cell of Comparative Example 2.
[0165] The performance of the pin-type perovskite solar cells of Examples 14 to 23 and Comparative Example 2 was tested. The test method is as follows, and the results are shown in Table 1.
[0166] (1) JV characteristic curve: The JV characteristic curve of the device was measured using a Keithley 2440 light source under a simulated AM1.5G spectrum.
[0167] The light intensity was calibrated using a solar simulator (Newport, 91160) from NREL using a standard silicon solar cell device. The effective measurement area was 0.07 cm 2 , under reverse and forward bias scans, the scan rate was 100mV / s and the bias range was from -0.2V to 1.2V.
[0168] Table 1. Performance of perovskite solar cells of Examples 14 to 23 and Comparative Example 2.
[0169] sample PCE(%) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) Voc(V) Embodiment 14 19.21 24.74 84.01 0.92 Embodiment 15 18.52 24.11 82.62 0.93 Example 16 18.21 23.57 84.02 0.92 Embodiment 17 17.87 23.63 83.13 0.91 Embodiment 18 18.31 24.05 82.79 0.92 Embodiment 19 18.33 24.02 82.95 0.92 Embodiment 20 18.14 23.86 82.68 0.92 Embodiment 21 18.05 23.58 82.35 0.93 Embodiment 22 18.06 23.84 83.27 0.91 Embodiment 23 18.19 23.81 83.08 0.92 Comparative Example 2 13.61 21.46 78.31 0.81
[0170] It can be seen from Table 1 that the benzothiadiazole copolymers prepared in Examples 4 to 13 of the present invention have higher Voc values and FF values when used to prepare perovskite solar cells, thereby obtaining a high PCE value.
[0171] The unpackaged pin-type perovskite solar cells of Examples 14 to 23 and Comparative Example 2 were placed in an atmospheric environment and stored for 30 days before being subjected to performance tests. The results are shown in Table 2.
[0172] Table 2. Performance of perovskite solar cells of Examples 14 to 23 and Comparative Example 2.
[0173] sample PCE(%) Embodiment 14 18.87 Embodiment 15 18.22 Example 16 18.06 Embodiment 17 17.43 Embodiment 18 17.98 Embodiment 19 18.09 Embodiment 20 18.01 Embodiment 21 17.87 Embodiment 22 17.94 Embodiment 23 18.03 Comparative Example 2 11.62
[0174] As shown in Tables 1 to 2, the benzothiadiazole copolymers prepared in Examples 4 to 13 of the present invention have high Voc values, Jsc values, and FF values for preparing perovskite solar cells, thereby obtaining high PCE values. The perovskite solar cells prepared from the benzothiadiazole copolymers obtained in Examples 4 to 13 of the present invention still maintain high energy conversion efficiency during long-term use, and can maintain high battery stability in an atmospheric environment for a long time.
[0175] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that after reading the specification of this application, the technicians can still modify or replace the specific implementation mode of the present invention with equivalents, but these modifications or changes do not deviate from the scope of protection of the pending claims of the present application.
Claims
1. A benzothiadiazole copolymer, characterized in that: The structural formula of the benzothiadiazole copolymer is shown in formula (I): Formula (I); Among them, x:y is 5~50:
1.
2. The benzothiadiazole copolymer according to claim 1, characterized in that The x:y is 20~45:
1.
3. The benzothiadiazole copolymer according to claim 1, characterized in that: The number average molecular weight of the benzothiadiazole copolymer is 12000-20000 g / mol, and the PDI is 1.5-2.
5.
4. The benzothiadiazole copolymer according to claim 1, characterized in that: The value range of x is 10~500, and the value range of y is 1~10.
5. The method for preparing the benzothiadiazole copolymer according to any one of claims 1 to 4, characterized in that: The steps include: A dibromo-substituted triphenylamine compound, a benzothiadiazole pinacol borate compound, a triphenylamine pinacol borate compound, an auxiliary agent and a palladium catalyst are mixed and reacted at elevated temperature to obtain a benzothiadiazole copolymer. The structural formula of the dibromo-substituted triphenylamine compound is shown in formula (II): Formula (II); The benzothiadiazole boronic acid pinacol ester compound is shown in formula (III): Formula (III); The triphenylamine boric acid pinacol ester compound is shown in formula (IV): Formula (IV).
6. The method for preparing a benzothiadiazole copolymer according to claim 5, characterized in that: The structural formula of the palladium catalyst is shown in formula (V): Formula (V).
7. The method for preparing a benzothiadiazole copolymer according to claim 5, characterized in that: The molar ratio of the dibromo-substituted triphenylamine compound, the benzothiadiazole boric acid pinacol ester compound, and the triphenylamine boric acid pinacol ester compound is 1-3:1-3:1-4; and / or, the ratio of the total mole of the dibromo-substituted triphenylamine compound, the benzothiadiazole pinacol borate compound and the triphenylamine pinacol borate compound to the mole of the palladium catalyst is 1:0.001-0.01; And / or, the reaction temperature is 80-120° C. and the reaction time is 12-32 hours.
8. The method for preparing a benzothiadiazole copolymer according to claim 5, characterized in that: The auxiliary agent includes an inorganic base, an organic phosphine, a quaternary ammonium salt and a solvent; The inorganic base is selected from at least one of potassium carbonate and potassium phosphate; The organic phosphine is selected from at least one of tri(2-furyl)phosphine and tributylphosphine; The quaternary ammonium salt is selected from at least one of tetrabutylammonium bromide and methyltrialkylammonium chloride; The solvent is a mixture of toluene and water; The volume ratio of toluene to water is 2-8:1-2.
9. The method for preparing a benzothiadiazole copolymer according to claim 8, characterized in that: The ratio of the total mole of the dibromo-substituted triphenylamine compound, the benzothiadiazole boronic acid pinacol ester compound and the triphenylamine boronic acid pinacol ester compound to the mole of the inorganic base is 1-1.5:1-1.5; and / or, the ratio of the total mole of the dibromo-substituted triphenylamine compound, the benzothiadiazole pinacol borate compound and the triphenylamine pinacol borate compound to the mole of the organic phosphine is 1.5-4.5:1; And / or, the ratio of the total mole of the dibromo-substituted triphenylamine compound, the benzothiadiazole boric acid pinacol ester compound and the triphenylamine boric acid pinacol ester compound to the mole of the quaternary ammonium salt is 1:0.01-0.
1.
10. Use of the benzothiadiazole copolymer prepared by the preparation method of the benzothiadiazole copolymer according to any one of claims 1 to 4 or the benzothiadiazole copolymer according to any one of claims 5 to 9 in preparing perovskite solar cells.